2013
DOI: 10.3126/ajn.v2i0.7532
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human urine as fertilizer on crop production

Abstract: Nutrient cycling in the soil-plant ecosystem is an essential component of sustainable agriculture. Human excreta though have high nutrient value is being neglected and simply dumped as waste. Out of the human excreta, urine has high nitrogenous fertilizer value than feces. Hence by separating urine in ECOSAN toilet, it can be of great use in fulfilling the fertilizer demand of the country. The main objective of this study is to assess the effect of human urine on crop yield and to find out the appropriate urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In a study carried out by (Upreti et al, 2011) with different crops (onion, potatoes, wheat, radish, rice), using mineral (NPK) and organic fertilizations (human urine), and with distinct spaces, it was observed that human urine positively affected the evaluated crops.…”
Section: Svmentioning
confidence: 99%
“…In a study carried out by (Upreti et al, 2011) with different crops (onion, potatoes, wheat, radish, rice), using mineral (NPK) and organic fertilizations (human urine), and with distinct spaces, it was observed that human urine positively affected the evaluated crops.…”
Section: Svmentioning
confidence: 99%
“…The firmly held belief that the Pahadi ruling elites misrecognized the Madhesi community and systematically excluded them from the national mainstream served as the foundation for the politics of recognition (Pandey, 2022;Sijapati, 2013). Put differently, historical exclusion and marginalization, and systemic structural discrimination of the Madhesi people set the conditions for the rise of the collective consciousness of a pan-Madhesi identity at the macro-level (Hachhethu, 2007;Jha, 2017;Mathema, 2011;Sah, 2017;Upreti et al, 2013). However, a gradually emerging dissension in the micro-politics of the Madhesi community -the political, economic, and sociocultural cleavages and confrontations posing problems to the pan-Madhesi identity -has not received the attention it deserves in scholarly discourse.…”
Section: Rethinking Madhesi Politics Of Recognitionmentioning
confidence: 99%
“…In Tarai-Madhes, social interactions are governed by caste distinctions, which also heavily influence political decisions and frequently influence economic stratification (ICG, 2007). Caste factors continue to significantly influence local and regional politics (Gaige, 2009;Upreti et al, 2013). While high-castes and some middle castes, such as Yadavs in the Tarai-Madhes, enjoy cultural, political, and economic privileges (Basnet, 2019), low-caste Madhesi have faced indignities of untouchability and social ostracization (Tewari, 2012).…”
Section: Rethinking Madhesi Politics Of Recognition 163mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the agents such as bacteria, protozoa, viruses and helminthes in excreta which cause diseases are usually shed in faeces rather than in urine (Hoglund et al 2002). As a result, the health risks which are associated with the consumption of urine for agricultural purposes have been found to be insignificant (Upreti et al 2011). The pathogens which cause venereal diseases can also be excreted through urine but there is no indication of whether they have a potential to thrive outside the human body and if this would be of any health significance (Hoglund et al 2002).…”
Section: Introductionmentioning
confidence: 99%